Assessment of quality of the crew piloting technique in the airline - Грищенко, Юрій Віталійович (Science-based technologies, 2020)
Safety of flights occupies an important place at air transportations. Modern aircrafts have high reliability of avionics and other systems. Aviation incidents carry improbable character, and about 80% them is on a human factor. Automation control of the aircraft unloads the crew from routine actions and frees up time for decision-making. At the same time, the crew experiences increased psychophysiological tension during the transition to control during approach in the director or helm control modes. Assessment of the quality of piloting techniques using probability theory methods during approach in the director mode is aimed at forecasting of crew actions in special flight cases. Only 2 % flights have remarks, rejections, violations, incidents, serious incidents, air accidents without human victims, air crash. The transition to the director mode does not mean that all automated control systems completely stop working. The pilot is considered with extended functions in the contour of an ergatic control system. Integrated flight simulators work out actions in special flight cases. This allows you to instill the skill of such actions and act confidently when such a situation arises in flight. However, the simultaneous combination of failures, which leads to increased psychophysiological tension of the human operator, is almost impossible to foresee. Thus, the crew needs not only to inculcate skills in actions in case of equipment failures, but also to train in controlled actions with increased psychophysiological tension. In our previous works, the approach paths in simple and complex conditions were considered. As a result of the analysis of correlation functions, the predicted boundaries of entry into the glide path were obtained depending on the influence of negative factors on the human operator. A negative effect on the pilot was noted the delay in entering the glide path. In this work, the theoretical conclusions made in previous studies are experimentally confirmed. Since the random roll angle function is ergodic and stationary in nature, an autocorrelation function is sufficient to analyze the quality of the piloting technique in one flight. When approaching on a shortened glide path, there is a big difference between the first maximum values of the first negative values of the autocorrelation functions of the roll angle from landing with a normal glide path. The Fourier transform of the amplitudes of our autocorrelation functions confirmed the above findings. It should be noted that the amplitude of the airplanes roll angle of the pilots fit into the requirements of the manual for flight operations during approach. The question is about proposals for assessing the characteristics of the erratic system in special flight cases conditions and the necessity for accuracy of entry to the glide path. The normal law of roll angle distribution confirmed the good quality of the crew piloting technique in the horizontal plane. The crew is estimated, as the co-pilot performs operations with the avionics systems while flying in the director’s airplane control mode without comment.